Intranasal Vaccination Strategy to Control the COVID-19 Pandemic from a Veterinary Medicine Perspective - Annas, Salleh (Animals (Basel), 2021)
SIMPLE SUMMARY: Intranasal vaccination is one of the methods used to stimulate mucosal immunity. It has been widely practised to control many human and animal respiratory diseases. Coronavirus disease 2019 (COVID-19) is a highly contagious respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which resulted in a global pandemic. COVID-19 has reminded some veterinarians of various contagious veterinary diseases, including coronavirus infections in animals. This article discusses the control of highly contagious diseases of veterinary importance with emphasis on an intranasal vaccination approach, and the potential of implementing similar strategies in human medicine to control the ongoing COVID-19 pandemic. ABSTRACT: The world is currently facing an ongoing coronavirus disease 2019 (COVID-19) pandemic. The disease is a highly contagious respiratory disease which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Current control measures used by many countries include social distancing, wearing face masks, frequent hand washing, self-isolation, and vaccination. The current commercially available vaccines are injectable vaccines, although a few intranasal vaccines are in trial stages. The reported side effects of COVID-19 vaccines, perceptions towards the safety of the vaccines, and frequent mutation of the virus may lead to poor herd immunity. In veterinary medicine, attaining herd immunity is one of the main considerations in disease control, and herd immunity depends on the use of efficacious vaccines and the vaccination coverage in a population. Hence, many aerosol or intranasal vaccines have been developed to control veterinary respiratory diseases such as Newcastle disease, rinderpest, infectious bronchitis, and haemorrhagic septicaemia. Different vaccine technologies could be employed to improve vaccination coverage, including the usage of an intranasal live recombinant vaccine or live mutant vaccine. This paper discusses the potential use of intranasal vaccination strategies against human COVID-19, based on a veterinary intranasal vaccine strategy.